The weight of the crisis: Evidence from newborns in Argentina - Carlos Bozzoli; Climent Quintana-Domeque (Institute for the Study of Labor (IZA), 2010)
Argentina hit headlines around the world in 2002 on account of the largest debt default in history and a sudden economic collapse that generated statistics reminiscent of those from the Great Depression. In this article we focus on other consequences of the crisis that are not so obvious but that may linger for decades. Combining macroeconomic indicators with the Argentine national registry of live births (approximately 1.9 million from 2001 through 2003), we show that the crisis led to an average birth-weight loss of 30 grams. Our estimate is robust to different identification strategies. This deterioration in birth weight occurred in only about six months, and represents one-sixth of the difference in average birth weight between American and Pakistani babies. We also find that the crisis affected particularly the weight of babies born of mothers of low socioeconomic status. In an attempt to estimate the long-term economic costs of the crisis, we simulate the average loss of future individual earnings due to the reduction in average birth weight: about 500 per live birth.
Keywords: I1; J1; 330; Argentina; birth weight; economic crisis; Kinder; Körpergewicht; Wirtschaftskrise; Staatsbankrott; Schätzung; Argentinien